Digital Optimization of Productive Waqf Management for the Economic Empowerment of the Ummah: A Case Study in Semarang City - Bahrul Fawaid; Mochamad Subchan Mauludin (Faculty of Law, Universitas Pekalongan, 2025)
Waqf plays a significant role in social and economic development, particularly in Muslim-majority countries like Indonesia. However, its utilization remains limited to traditional sectors such as places of worship and education, while its potential for economic activities remains underdeveloped. This study aims to explore the management of productive waqf in Semarang City through Islamic financing and digitalization approaches. This research employs a qualitative method with a normative-empirical approach, analyzing waqf regulations and the implementation of digitalization. The results show that out of 2,175 waqf land plots in Semarang, the majority are not yet managed productively. Islamic financing models such as ijarah, musyarakah, and cash waqf can be applied to optimize waqf utilization. Additionally, digitalization facilitates collaboration between waqif, nazhir, and investors, enhancing transparency and management efficiency. In conclusion, with Islamic financing models and digitalization, the potential of productive waqf in Semarang City can be optimized, providing a positive impact on societal welfare and economic empowerment.